A study of tenants’ maintenance awareness, responsibility and satisfaction in institutional housing in Nigeria - Oladapo, Adebayo A. (International Journal of Strategic Property Management, 2010)
The housing problem in Nigeria is both quantitative and qualitative. The qualitative aspect, which has to do with the maintenance of the existing stock, has assumed greater significance because of the need to preserve the existing stock and bring it to acceptable standards of living. Tenants in institutional housing are major stakeholders who directly bear the brunt of the disrepair of the houses. Hence they have a role to play to optimise the maintenance of their houses within the very limited resources available to the maintenance departments. The study was carried out to evaluate the maintenance awareness and responsibilities of tenants and quantitatively analyse their satisfaction with the state of maintenance of their houses. The results showed that the tenants had a high level of maintenance awareness and responsibility but their satisfaction with the maintenance of their houses was just average.First Published Online: 18 Oct 2010